Evaluation of Interleukin-6 In Tears and Serum and Its Associated Factors in Age Related Macular Degeneration Patients - Rosli, Abdul Hadi (2021)
OBJECTIVE: The objective of this study was to evaluate the Interleukin-6 (IL-6) in tears and serum in age related macular degeneration (AMD) patients and to determine its associated factors. METHODS: This was a comparative cross-sectional study. Patients with Early AMD, Late AMD and Control group whom fulfilled the inclusion criteria were recruited into this study. Tears and serum samples were collected. The samples were analysed using commercial Human IL-6 enzyme-linked immunosorbent assay kit to measure IL-6 levels in tears and serum. Only late neovascular AMD (nAMD) was enrolled in this study since there was no late dry AMD available during the study period. RESULTS: A total of 142 patients (56 early AMD, 56 late nAMD and 30 Control group) were recruited in this study. AMD showed significantly higher mean tears IL-6 (21.91 (95%CI: 19.89, 23.93), p= 0.014) and serum IL-6 (12.01 (95%CI: 10.93, 13.08), p= 0.004) compared to control group after adjusted with covariates. Only mean serum IL-6 level was significantly in late nAMD (13.97 (95%CI: 12.43, 15.52), p= 0.001) compared to early AMD after adjusted with covariates. There was no significant association found between IL-6 level in tears with duration of AMD, serum level of IL-6, smoking status and AMD status. CONLUSION: IL-6 in tears and serum showed significant elevation among AMD. Therefore, tears sample can be used as non-invasive biomarker for AMD screening.